2018
DOI: 10.1186/s13071-018-2660-8
|View full text |Cite
|
Sign up to set email alerts
|

Fresh insights into the pyrimidine metabolism in the trypanosomatids

Abstract: The trypanosomatid parasites continue their killing spree resulting in significant annual mortality due to the lack of effective treatments and the prominence of these diseases in poorer countries. These dimorphic parasites thrive unchecked in the host system, outsmarting the immune mechanisms. An understanding of biology of these parasitic forms will help in the management and elimination of these fatal diseases. Investigation of various metabolic pathways in these parasites has shed light in the understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 91 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…In this regard, it is somewhat unexpected that only two enzymes (adenylosuccinate synthetase (ADSS) and inosine monophosphate dehydrogenase (IMPDH)) were identified in the L. tarentolae glycosomal proteome, and five of these enzymes were identified in the glycosomal fractions of L. donovani. Similarly, we identified most of the enzymes constituting the de novo pyrimidine biosynthesis pathway (Table 4) [59] in the L. infantum proteome, whereas Jamdhade et al [57] only found one enzyme of this pathway in the L. donovani glycosomal proteome-the orotate phosphoribosyltransferase (LDBPK_160560). All the enzymes (grey squares) that are required to complete the pathway were identified in this study.…”
Section: Components Of the Proteostasis Networkmentioning
confidence: 72%
“…In this regard, it is somewhat unexpected that only two enzymes (adenylosuccinate synthetase (ADSS) and inosine monophosphate dehydrogenase (IMPDH)) were identified in the L. tarentolae glycosomal proteome, and five of these enzymes were identified in the glycosomal fractions of L. donovani. Similarly, we identified most of the enzymes constituting the de novo pyrimidine biosynthesis pathway (Table 4) [59] in the L. infantum proteome, whereas Jamdhade et al [57] only found one enzyme of this pathway in the L. donovani glycosomal proteome-the orotate phosphoribosyltransferase (LDBPK_160560). All the enzymes (grey squares) that are required to complete the pathway were identified in this study.…”
Section: Components Of the Proteostasis Networkmentioning
confidence: 72%
“…In fungi, a similar protein exists but lacks the dihydroorotase function, while in bacteria, archaea, and other eukaryotes, the first three reactions of the pathway are carried out by three separate proteins [96]. In trypanosomatids, these are also catalyzed by three independent enzymes, which in some species form multiprotein complexes [96,99].…”
Section: Nucleotide Metabolismmentioning
confidence: 99%
“…In trypanosomatids, the last step of the UMP biosynthesis is catalyzed by a glycosomal bifunctional enzyme comprised of orotate phosphoribosyltransferase (OPRT) and orotidine 5′-monophosphate decarboxylase (OMPDC) fused in the reverse order (pyrF/E, or OPRT/OMPDC) as compared to its metazoan counterpart called uridine-monophosphate synthase (UMPS; pyrE/F, or OMPDC/OPRT) [99]. Euglenozoa show a complex pattern of UMP synthesis, since we have identified separate transcripts encoding pyrF and pyrE genes, as well as their fusions (Additional file 9: Table S7).…”
Section: Nucleotide Metabolismmentioning
confidence: 99%
“…In this regards, it is somewhat unexpected that only two enzymes (ADSS and IMPDH) were identified in the L. tarentolae glycosomal proteome, and five of these enzymes in the glycosomal fractions of L. donovani. Similarly, we have identified in the L. infantum proteome most of the enzymes constituting the de novo pyrimidine biosynthesis pathway (Table 4) [59], whereas Jamdhade et al [57], in the L. donovani glycosomal proteome, only found one enzyme of this pathway, the orotate phosphoribosyltransferase (LDBPK_160560). Peer-reviewed version available at Genes 2020, 11, 1036; doi:10.3390/genes11091036…”
Section: Glycosomal Proteins Represent a Substantial Fraction Of The mentioning
confidence: 66%